Cow Protection Movement during the British Rule in India - Hassan, Syed Minhaj ul Hassan; Yasmeen, Samina (Ancient Pakistan, 2021)
India is home to followers of different religions but the majority professes to Hinduism. Muslim is the largest minority in India, who in spite of being in minority ruled India for hundreds of years. During the long rule of the Muslims in India, the Hindus remained subservient and passive. Once the Muslims lost their rule to the British, the Hindus slowly and gradually started asserting themselves which happens to be at the cost of Muslims. One such example is that of the issue of slaughtering of cow. Since the Muslims' religion permits the eating of cow meat, it is widely slaughtered during Bakr Id and other festivities. This act on the part of Muslims has always resulted in strong criticism from the Hindus and even resulted in violent riots. . . .